Clinical Characteristics and Maternal–Fetal Outcomes of Severe Preeclampsia Referral Cases at Waled General Hospital: A Retrospective Study - Agus Haerani; Akhmad Yogi Pramatirta; Wildan A Sutrisno (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Objective: Severe preeclampsia remains a major contributor to maternal and perinatal morbidity and mortality, particularly in developing countries, where delayed referral and inadequate early detection are common. This study aimed to describe the clinical characteristics and maternal–fetal outcomes of severe preeclampsia cases referred to Waled General Hospital.Method: A retrospective descriptive study was conducted using secondary data from medical records and maternal health (KIA) books for pregnant women diagnosed with severe preeclampsia and referred to Waled General Hospital from January to December 2024. Collected data included maternal demographic characteristics, gestational age, laboratory findings, maternal risk factors, and maternal–fetal outcomes.Result: A total of 76 pregnant women with severe preeclampsia were included, with a mean maternal age of 33.3 years. Most participants were multiparous (75%), and 40.8% had extreme maternal age (<20 or >35 years). Proteinuria was present in 69.7% of cases, and fetal complications were more frequent than maternal complications, particularly prematurity (13.2%), followed by intrauterine growth restriction (6.6%) and intrauterine fetal death (2.6%).Conclusion: Severe preeclampsia referral cases at Waled General Hospital were marked by substantial maternal risk factors and adverse maternal–fetal outcomes, particularly prematurity. Strengthening early detection, clinical assessment, and timely referral may improve maternal and perinatal outcomes.Karakteristik Klinis dan Luaran Maternal–Fetal Kasus pada Rujukan Preeklamsia Berat di RSUD Waled Cirebon: Studi RetrospektifAbstrakTujuan: Preeklamsia berat masih menjadi penyebab utama morbiditas dan mortalitas maternal serta perinatal, terutama di negara berkembang yang sering menghadapi keterlambatan deteksi dini dan rujukan. Penelitian ini bertujuan untuk mendeskripsikan karakteristik klinis dan luaran maternal–fetal pada kasus rujukan preeklamsia berat di RSUD Waled.Metode: Penelitian deskriptif retrospektif dilakukan menggunakan data sekunder berupa rekam medis dan buku Kesehatan Ibu dan Anak (KIA) pasien hamil dengan diagnosis preeklamsia berat yang dirujuk ke RSUD Waled pada periode Januari hingga Desember 2024. Data yang dikumpulkan meliputi karakteristik demografis maternal, usia kehamilan, temuan laboratorium, faktor risiko maternal, serta luaran maternal–fetal.Hasil: Sebanyak 76 ibu hamil dengan preeklamsia berat diikutsertakan dalam penelitian dengan rerata usia maternal 33,3 tahun. Mayoritas pasien merupakan multipara (75%), dengan hampir setengahnya (40,8%) berada pada kelompok usia maternal ekstrem, yaitu berusia <20 tahun atau >35 tahun. Proteinuria ditemukan pada 69,7% kasus, dan komplikasi fetal lebih sering ditemukan dibandingkan komplikasi maternal, terutama prematuritas (13,2%), restriksi pertumbuhan intrauterin (6,6%), dan kematian janin intrauterin (2,6%).Kesimpulan: Kasus rujukan preeklamsia berat di RSUD Waled ditandai oleh tingginya faktor risiko maternal serta luaran maternal–fetal yang merugikan, terutama prematuritas. Penguatan deteksi dini, penilaian klinis, dan rujukan yang tepat waktu berpotensi meningkatkan luaran maternal dan perinatal.